Preparation method and application of metal compound composite tin oxide nano colloidal dispersion liquid
By introducing amphoteric metal compounds into the tin dioxide colloidal dispersion, the acid ions generated by hydrolysis combine with the defects of tin oxide nanoparticles, the electrostatic repulsion potential energy is enhanced, and the stability and charge recombination problems of tin dioxide nanoparticles are solved, forming high performance The composite film is suitable for perovskite solar cells.
Patent Information
- Application Number
- CN202411212412.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
AI Technical Summary
In practical applications, tin dioxide nanoparticles have problems such as insufficient stability, easy agglomeration and charge recombination, and the prior art is difficult to effectively solve these problems.
The alkaline tin oxide colloidal dispersion is introduced to the alkaline tin oxide colloidal dispersion. The metallic acid ions produced by hydrolysis are combined with oxygen vacancies and surface hydroxyl defects, which enhance the electrostatic repulsion potential energy, inhibit the agglomeration of nanoparticles, and improve the dispersion liquid and annealing to form a composite film with high conductivity and low defect density.
It significantly improves the stability of the tin dioxide nanocolloid dispersion, enhances the conductivity and density of the film, reduces defect density, is suitable for perovskite solar cells, and improves the performance and life of the device.
Smart Images

Figure CN119136627A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of semiconductor nanomaterials, and specifically relates to a method for preparing a metal compound composite tin oxide nanocolloid dispersion, and the application of the metal compound composite tin oxide nanocolloid dispersion in the fields of chemical sensors, solar cells, recyclable power supply electrodes, integrated circuits, etc. Background Art
[0002] Nanoparticles are objects between macroscopic matter and atomic or molecular matter, composed of hundreds to thousands of atoms, with at least one dimension being nanometer size (1-100nm). Nanomaterials have the characteristics of small particle size, large specific surface area, high surface energy, large proportion of surface atoms, and three unique effects: surface effect, small size effect and macroscopic quantum tunneling effect, making nanoparticles have both basic value and application value, and are widely studied by more and more scientists.
[0003] Tin dioxide nanoparticles (SnO2 NCs) have shown attractive application prospects in transparent electrodes, gas sensors, storage materials, and solar cells due to their wide band gap, unique optical properties, electrical properties, and chemical stability. They are considered to be one of the most promising semiconductor nanomaterials. Unfortunately, SnO2 nanoparticles have tin vacancies (V O 、V Sn ), interstitial atoms (O i Sn i ), antisite defect (Sn O , O Sn ) and terminal hydroxyl group (OH T ) and bridging hydroxyl groups (OH B ) and other defects, while giving tin oxide n-type semiconductor characteristics, it also causes serious charge recombination, and tin dioxide nanocolloid dispersions face problems such as insufficient stability and easy agglomeration of particles in practical applications (references: DOI: 10.1021 / jp807753t; 10.1002 / adma.202005504; 10.1021 / acsenergylett.0c01566). Therefore, it is of great significance to develop a composite tin oxide preparation method with cheap raw materials, simple process and easy promotion to solve the above problems. Through the composite metal compound, the stability of the colloidal dispersion is significantly improved, the defects are effectively passivated, the conductivity is improved, and the energy band can also be effectively adjusted to meet the needs of various application scenarios.
[0004] To this end, an invention patent with a publication number of CN114249956A in the prior art discloses a surface-modified metal oxide nanoparticle dispersion composition and a preparation method thereof, a film composition and an optical film. According to an embodiment of the invention, the surface-modified metal oxide nanoparticle dispersion composition comprises: metal oxide particles surface-modified with a phosphoric acid compound; an acrylate monomer; and a silane coupling agent. The metal oxide particles include at least one selected from the group consisting of ZrO2, SiO2, TiO2, SrTiO2, MgO, Ta2O5, ZrO2-TiO2 and SiO2-Fe2O3. In the step of forming the reactant, an alkaline aqueous solution can be added dropwise to an aqueous solution of a phosphoric acid compound added with the metal oxide nanoparticles, and then maintained at a reaction temperature of 70°C to 100°C for 2 to 4 hours. On the one hand, the patent uses a phosphoric acid organic compound to surface-modify a high-refractive inorganic material to achieve a high refractive index, high transparency, and reduce the occurrence of yellowing, wherein the organic compound modification used has poor stability. Secondly, this patent, like most existing technical solutions, basically focuses on a method for preparing a high-refractive index, high-transparency surface-modified metal oxide nanoparticle dispersion composition, but does not focus on the problems existing in the colloidal dispersion of high-refractive index metal oxides (such as SnO2) itself. Summary of the invention
[0005] A brief summary of embodiments of the present invention is provided below to provide a basic understanding of certain aspects of the present invention. It should be understood that the following summary is not an exhaustive summary of the present invention. It is not intended to identify key or important parts of the present invention, nor is it intended to limit the scope of the present invention. Its purpose is merely to provide certain concepts in a simplified form as a prelude to a more detailed description discussed later.
[0006] To solve the above problems, the present invention provides a preparation method and application of a metal compound composite tin oxide nano-colloid dispersion, the stability of the metal compound composite tin oxide nano-colloid dispersion is significantly improved, oxygen vacancies and surface hydroxyl defects are effectively passivated, and the obtained film has significantly improved conductivity, low defect density and uniform and dense morphology, and is applied in perovskite solar cells, showing good performance. To achieve the above purpose, the idea of the present invention is: an amphoteric metal compound that can be hydrolyzed in an alkaline environment is introduced into an alkaline tin oxide nano-colloid dispersion, and the metal acid radical ions produced by hydrolysis tend to bind to positively charged defect sites (such as oxygen vacancies), enhance the electrostatic repulsion potential of the tin dioxide colloidal dispersion, and weaken the interaction between adjacent tin dioxide nanoparticles as a stabilizer, inhibit nanoparticle agglomeration, improve the stability of the colloidal dispersion, and passivate the surface defects of tin dioxide nanoparticles. After annealing in air, a composite tin dioxide film with high conductivity, low defect density and uniform and dense is formed.
[0007] As one aspect of the present application, a method for preparing a metal compound composite tin oxide nano-colloid dispersion is provided, comprising the following steps:
[0008] Step 1: obtaining an alkaline tin dioxide colloidal dispersion;
[0009] Step 2: Preparation of aqueous dispersion of amphoteric metal compound: The amphoteric metal compound is formulated into aqueous dispersion of amphoteric metal compound with different concentrations of 0.5-5 mg / ml, and stirred at room temperature for a preset time (e.g., 3-5 h); the aqueous dispersion of amphoteric metal compound has a plurality of types of amphoteric metal compounds, and each amphoteric metal compound has a plurality of aqueous dispersions at different concentrations; in addition, the concentration range of 0.5-5 mg / ml here is to take the same volume of 200 μL of metal compound aqueous dispersion into 1 ml of tin oxide colloidal dispersion to prepare metal compound composite tin oxide colloidal dispersions of different concentrations. The optimal concentration of different metal compounds is different, which is related to the solubility, particle size, charge density and other factors of the metal compound. The optimal concentration ratio should be optimized according to the parameters of the conductivity, electron mobility and morphological characteristics of the prepared film.
[0010] Step 3: Preparation of metal compound composite tin oxide colloidal dispersion: Take the same volume of 200 μL of solution from the amphoteric metal compound aqueous dispersions of different concentrations and add them to 1 ml of alkaline tin dioxide colloidal dispersion, place them in an ultrasonic device for ultrasonic dispersion at room temperature for a preset time (e.g., 1-2 h), and avoid boiling of water in the ultrasonic device, so as to obtain a metal compound composite tin oxide precursor solution;
[0011] Step 4: Deposition of metal compound composite tin oxide film: Spin-coat the metal compound composite tin oxide precursor solution prepared in step 3 on the substrate surface, and anneal to form a composite tin oxide film. The annealing temperature is 145°C-155°C, and the time is 25-35 minutes, for example, annealing at 150°C for 30 minutes.
[0012] Furthermore, before the metal compound composite tin oxide precursor solution of step 3 is spin-coated on the substrate surface, the following treatment is also performed: the substrate is placed in ultraviolet-ozone plasma treatment for several minutes to enhance the wettability of the substrate. After the plasma-treated substrate is taken out, a certain amount of the metal compound composite tin oxide colloidal dispersion is taken with a pipette gun, and a thin film is obtained by spin coating.
[0013] As an implementation scheme, in step 1, the alkaline tin dioxide colloidal dispersion is obtained by purchasing a commercial Alfa tin dioxide colloidal dispersion, then diluting it in a mass ratio of 1:3 between tin oxide and deionized water and stirring it at room temperature; or it can be synthesized by the following steps:
[0014] Tin oxide gel (SnO2·nH2O, n≤2) was obtained by mixing NH4HCO3 (1.0 mol / L) and SnCl4 (1.0 mol / L) aqueous solutions in a ratio of 1:1 through hydrolysis condensation reaction. The specific reaction process is described by the reaction formula:
[0015] SnCl4+4NH4CO3→SnO2·nH2O+4NH4Cl+4CO2+(2-n)H2O;
[0016] The above reaction is first stirred in an ice bath for a preset time (e.g., 3 hours), and then stirred at room temperature for a preset time (e.g., 10 hours) to generate a milky white gel; the generated milky white gel is centrifugally washed with deionized water for several times (e.g., 5 times) to obtain a wet gel, and the washed wet gel is redispersed in a mixed solution of potassium hydroxide (2 mg / ml, which is determined according to the pH value of KOH) and ammonia water (PH=12), wherein the volume ratio of potassium hydroxide to ammonia water is 1:2, and a mixed dispersant of PVP and CTAB with a mass fraction of 0.15% (wherein m(PVP):m(CTAB)=2:1) is added, and the reaction is stirred for a preset time (e.g., 3 hours) to obtain a clear and transparent colloidal dispersion (mass fraction is 3.75%);
[0017] As an implementation scheme, in step 2, the amphoteric metal compound hydrolyzed in an alkaline environment can be: AlCl3, SbCl3, ZnO, Al2O3, Sb2O3, TiO2, Nb2O5, Sb2O5, WO3, MoO3, etc.
[0018] According to another aspect of the present application, there is provided an application of a metal compound composite tin oxide colloidal dispersion in a chemical sensor, a solar cell, a recyclable power supply electrode, and an integrated circuit.
[0019] According to another aspect of the present application, a film made of a metal compound composite tin oxide colloidal dispersion is provided.
[0020] In practical applications, the lattice mismatch between the perovskite absorption layer and the SnO2 electron transport layer at the contact interface can lead to high-density trap states, which not only affects the charge transfer at the interface, but also may lead to ion migration, making the perovskite film easy to react with water and oxygen, causing device degradation. The present invention prepares aqueous dispersions of amphoteric metal compounds of different concentrations, and then takes a number of amphoteric metal compound aqueous dispersions of different concentrations and adds them to alkaline tin dioxide colloidal dispersions to obtain a metal compound composite tin oxide precursor solution. The amphoteric metal compound is introduced into the alkaline tin dioxide colloidal dispersion to prepare the corresponding Mx@SnO2 composite film, and the metal acid ions (such as Sb(OH)4) generated by the hydrolysis of the amphoteric metal compound in the alkaline solution - ) has a direct impact on the alkaline tin dioxide colloidal dispersion. When the amphoteric metal compound aqueous dispersion is added to the alkaline tin dioxide colloidal dispersion, no precipitate or opaque aggregate will be produced in the solution because of the hydrolysis reaction and the increase in electrostatic repulsion potential. The metal acid ions produced by hydrolysis tend to bind to positively charged defect sites (such as V O s) and act as a stabilizer to reduce the interaction between adjacent SnO2 nanocrystals, thereby promoting the uniform and stable dispersion of SnO2 NCs. After annealing in air, the deposited Mx@SnO2 films exhibited significantly enhanced conductivity, compactness, and uniformity compared to unmodified SnO2. In addition, due to the suppression of inhomogeneous nucleation, perovskite layers with large grains and low defect density can be obtained. The results show that the defect state density of perovskite films (PVSK) based on Sb2O5@SnO2 electron transport layer (ETL) increased from 9.89×10 15 cm -3 Reduced to 7.31×10 15 cm -3 The defects on the PVSK / ETL interface are reduced and the contact is improved, which is beneficial to the transfer of charges and inhibits carrier recombination. The device achieves an open circuit voltage (V) of up to 1.20V. OC ) and a power conversion efficiency (PCE) of 24.54%.
[0021] In addition, in order to understand the effect of amphoteric metal compounds on alkaline tin dioxide colloidal dispersions, the particle size and stability of alkaline tin dioxide colloidal dispersions with different aging times and containing different concentrations of amphoteric metal compounds were characterized and analyzed by dynamic light scattering (DLS) and Zeta potential. We observed that the unmodified SnO2 NCs colloidal dispersion showed two Gaussian distributions (5±10nm and 60±10nm) after aging for 100 days, which were attributed to SnO2 single particles and clusters, respectively. It is worth noting that the particle size of SnO2 NCs doped with metal compounds does not change significantly. This phenomenon indicates that metal acid ions can be adsorbed on the surface of positively charged SnO2 NCs through electrostatic interaction, enhancing the electrostatic repulsion potential, weakening the interaction between adjacent SnO2 NCs, and inhibiting their agglomeration. The composite SnO2 colloidal dispersion with the optimal doping concentration maintains a high zeta potential of -40 to -50 mV, which is conducive to obtaining a stable and well-dispersed SnO2 precursor. Moreover, the prepared composite film has a denser and uniform morphology, which can effectively enhance the interface contact with the perovskite absorption layer and reduce leakage current.
[0022] The present invention introduces amphoteric metal compounds into an alkaline tin oxide colloidal dispersion, and the acid radical ions generated by hydrolysis are adsorbed on the surface of tin oxide nanoparticles, thereby enhancing the electrostatic repulsion potential of the tin oxide colloidal dispersion, weakening the interaction between tin oxide nanoparticles, inhibiting their agglomeration, and effectively passivating oxygen vacancies and surface hydroxyl groups. Therefore, the prepared composite film has a more compact and uniform morphology, can effectively enhance the interface contact with the perovskite absorption layer, and reduce leakage current; in addition, due to the passivation of defects and the reduction of charge recombination, the conductivity and carrier mobility of the film are significantly improved, which is conducive to the extraction and collection of photogenerated electrons in the perovskite layer, reducing non-radiative recombination and reducing resistance loss; the preparation process of the present invention is simple and easy, and has broad application prospects. The inorganic compound modification used in the present invention is more stable than the organic compound of the prior art, and focuses on the existing problems of the tin oxide colloidal dispersion. Starting from the DLVO theory, a method for introducing amphoteric metal compounds to obtain a high-performance tin oxide colloidal dispersion is provided.
[0023] In summary, the present invention realizes a tin oxide-based composite metal compound nano-colloidal dispersion and a preparation method thereof through the above-mentioned scheme. The obtained tin oxide composite metal compound nano-colloidal dispersion has significantly improved stability and effectively passivates the inherent defects of tin oxide nanoparticles. It has the characteristics of cheap raw materials, simple process, easy promotion, and excellent electrochemical properties of materials. It provides a new method for preparing composite metal compound thin film materials and has the potential for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention may be better understood by referring to the following description in conjunction with the accompanying drawings, wherein the same or similar reference numerals are used throughout the drawings to represent the same or similar components. The accompanying drawings, together with the following detailed description, are incorporated in and form a part of this specification and are used to further illustrate the preferred embodiments of the present invention and to explain the principles and advantages of the present invention.
[0025] In the figure:
[0026] Figure 1 This is a schematic diagram comparing the stability test of the colloidal dispersion of Example 1 and Comparative Example 1;
[0027] Figure 2 The distribution of the particle size of nanoparticles in the colloidal dispersion of Example 1 and Comparative Example 1;
[0028] Figure 3 Schematic diagram of SEM comparison of the films of Example 2 and Comparative Example 2;
[0029] Figure 4 Schematic diagram of photoluminescence spectrum test of the thin films of Example 2 and Comparative Example 2;
[0030] Figure 5 This is a schematic diagram comparing the photoelectric conversion efficiency test of the device of Example 2 and Comparative Example 2;
[0031] Figure 6 Schematic diagram of conductivity test of the thin films of Example 3 and Comparative Example 3;
[0032] Figure 7 Schematic diagram of the preparation of alkaline tin oxide colloidal dispersion of complex metal compounds. DETAILED DESCRIPTION
[0033] Embodiments of the present invention will be described below with reference to the accompanying drawings. Elements and features described in one drawing or one embodiment of the present invention may be combined with elements and features shown in one or more other drawings or embodiments. It should be noted that for the purpose of clarity, the representation and description of components and processes that are not related to the present invention and are known to those of ordinary skill in the art are omitted in the drawings and descriptions.
[0034] The embodiment of the present invention provides a tin oxide-based composite metal compound nano-colloidal dispersion, a preparation method and application thereof. The metal compound composite tin oxide nano-colloidal dispersion achieved by the scheme of the present invention has significantly improved stability and effectively passivates the inherent defects of tin oxide nanoparticles. It has the characteristics of cheap raw materials, simple process, easy promotion and excellent electrochemical properties of materials. It provides a new method for preparing composite metal compound thin film materials and has the potential for large-scale application.
[0035] The DLVO theory provides an intuitive framework for understanding and predicting the stability of charge-stabilized dispersions such as colloidal solutions. In this theory, the total interaction energy between two particles in a dispersion is a function of the sum of the van der Waals attraction (VdW) and the electrostatic repulsion, expressed as V tot =V VdW +V elec , van der Waals force (VdW) shows strong attraction at short distances and can still work even at relatively large particle spacing. It is a long-range but weak force. Electrostatic interaction dominates when the particle spacing is moderate, especially when the ion clouds formed by the charges on the particle surface begin to overlap with each other. The overlap of the double electric layer leads to a strong increase in repulsive potential, preventing the particles from getting closer. Depending on the pH value of the solution, the charge properties of the particle surface will change: the particles are positively charged at low pH values and negatively charged at high pH values. Therefore, amphoteric metal compounds are introduced into the alkaline tin oxide nanocolloid dispersion. The metal acid ions generated by hydrolysis combine with the positive potential defects on the surface of the tin oxide nanoparticles, which enhances the electrostatic repulsive potential of the colloidal dispersion, weakens the interaction between the particles, thereby inhibiting the agglomeration of the nanoparticles and improving the stability of the dispersion. At the same time, the metal acid ions can effectively passivate defects such as oxygen vacancies and hydroxyl groups, reducing charge recombination centers. This process helps to form a more uniform and dense film structure, improves the conductivity of the film, and achieves effective regulation of the energy band. The preparation method involves multiple steps, including the synthesis of alkaline tin oxide colloidal dispersion, the dilution of commercial tin dioxide colloidal dispersion, the preparation of amphoteric metal compound aqueous dispersion, etc. It is necessary to strictly control the reaction conditions, concentration and time, and find the right type of metal compound to ensure the quality and performance of the final film.
[0036] The above technical difficulties and innovations make this description forward-looking and groundbreaking, because in the past studies, few people have explored the use of the unique properties of amphoteric metal compounds, which can generate metal acid ions by hydrolysis in an alkaline environment and generate metal compounds by heating and annealing, to improve the stability of nanoparticle colloidal dispersions and prepare high-quality composite tin oxide films. This innovative idea and technical solution is based on a deep understanding of colloidal science and film preparation technology. Therefore, this description provides a novel and effective solution, bringing new progress and application prospects to this field.
[0037] Example 1
[0038] Specifically, the embodiment of the present invention provides a method for preparing a composite tin oxide nano-colloid dispersion, which comprises:
[0039] Step (1): Preparation of aluminum chloride aqueous solution: Prepare an aluminum chloride aqueous solution with a concentration of 0.5-5 mg / ml and stir at room temperature for 3 h;
[0040] Step (2): Synthesis of alkaline tin oxide colloidal dispersion: Mix aqueous solutions of NH4HCO3 (1.0 mol / L) and SnCl4 (1.0 mol / L), stir and react in an ice bath for 3 hours, then stir and react at room temperature for 10 hours, and obtain a milky white tin oxide gel (SnO2·nH2O, n≤2) through hydrolysis and condensation reaction. Wash the gel with deionized water by centrifugation for 5 times, and redisperse the washed wet gel in a mixed solution of potassium hydroxide (2 mg / ml) and ammonia water (PH=12) (the volume ratio of potassium hydroxide to ammonia water is 1:2), and add a mixed dispersant of PVP and CTAB with a mass fraction of 0.15% (wherein m(PVP):m(CTAB)=2:1), stir and react for 3 hours, and obtain a clear and transparent colloidal dispersion (mass fraction is 3.75%), which is filtered with a filter membrane with a pore size of 0.45 μm for standby use;
[0041] Step (3): Preparation of metal compound composite tin oxide colloidal dispersion: 200 μL of aluminum chloride aqueous solution of different concentrations (preferably 2 mg / ml) is added to the alkaline tin dioxide nano-colloidal dispersion of step (2) with a volume of 1 ml, and ultrasonically dispersed in an ultrasonic device for 1 hour at room temperature to avoid boiling of water in the ultrasonic device. After the ultrasonication is completed, the dispersion is allowed to stand for observation.
[0042] Comparative Example 1
[0043] Synthesis of alkaline tin oxide colloidal dispersion: Mix aqueous solutions of NH4HCO3 (1.0 mol / L) and SnCl4 (1.0 mol / L), stir and react in an ice bath for 3 hours, then stir and react at room temperature for 10 hours, and obtain a milky white tin oxide gel (SnO2·nH2O, n≤2) through hydrolysis and condensation reaction. Wash the gel by centrifugation with deionized water for 5 times, and redisperse the washed wet gel in a mixed solution of potassium hydroxide (2 mg / ml) and ammonia water (PH=12) (the volume ratio of potassium hydroxide to ammonia water is 1:2), and add a mixed dispersant of PVP and CTAB with a mass fraction of 0.15% (wherein m(PVP):m(CTAB)=2:1), stir and react for 3 hours, and obtain a clear and transparent colloidal dispersion (mass fraction is 3.75%), which is then allowed to stand for observation.
[0044] Figure 1The figure shows the initial (left) [SnO2]Al(OH)4-, SnO2 and the solution state after 100 days (right). As shown in the figure, the long-term stability of the tin oxide nano-colloid dispersion and the metal compound composite tin oxide nano-colloid dispersion was compared. The results showed that after 100 days of static storage, the unmodified tin oxide nano-colloid dispersion turned white, indicating that the nanoparticles agglomerated and the colloidal dispersion was unstable, while no obvious changes were observed in the metal compound composite tin oxide nano-colloid dispersion.
[0045] like Figure 2 As shown in Figure 3, from dynamic light scattering (DLS), we observed that the SnO2 nanocolloid dispersion showed two Gaussian distributions (5 ± 10 nm and 60 ± 10 nm) after aging for 100 days, which were attributed to SnO2 single particles and clusters, respectively. It is worth noting that the particle size of SnO2 NCs doped with AlCl3 did not change significantly.
[0046] The above phenomenon shows that Al(OH)4 - Anions can be adsorbed on the surface of positively charged SnO2 NCs through electrostatic interactions, weakening the mutual attraction (van der Waals force) between adjacent SnO2 NCs, enhancing the electrostatic repulsion potential energy, and inhibiting their agglomeration, which is beneficial to obtain stable SnO2 precursors.
[0047] Example 2
[0048] This embodiment provides a method for constructing a perovskite solar cell based on a Sb2O5@SnO2 composite metal compound electron transport layer, which includes:
[0049] Step (1): Preparation (FAPbI3) 0.9 (MAPbBr3) 0.1 Precursors: PbI2 concentration is 1.53M, PbBr2 concentration is 0.11M, FAI concentration is 1.4M, MABr concentration is 0.11M, MACl concentration is 0.5M, solvent is N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the solvent volume ratio is 9:1, and stirred for 12 to 24 hours to obtain a usable perovskite precursor solution;
[0050] Step (2): Preparation of antimony trichloride aqueous dispersion: prepare antimony trichloride aqueous dispersion with a concentration of 0.5-5 mg / ml, and stir at room temperature for 3 hours;
[0051] Step (3): prepare and dilute a commercial tin dioxide nanoparticle colloidal dispersion (15 wt%), dilute it according to the ratio of tin oxide colloidal dispersion to deionized water (1:3 mass ratio), stir it at room temperature for 12 hours, and filter it with a filter membrane with a pore size of 0.45 μm for later use;
[0052] Step (4): Preparation of Sb2O5@SnO2 metal compound composite tin oxide precursor solution: 200 μL of antimony chloride aqueous dispersion with different concentrations (preferably 3 mg / ml) is added to 1 ml of alkaline tin dioxide nano-colloid dispersion in step (3), and ultrasonically dispersed in an ultrasonic device for 1 hour at room temperature to avoid boiling of water in the ultrasonic device. After the ultrasonication is completed, filter with a filter membrane with a pore size of 0.45 μm for standby use;
[0053] Step (5): using FTO conductive glass as substrate and transparent electrode, with a transmittance of 80% and a surface resistance of 15Ω;
[0054] Step (6): Deposition of Sb2O5@SnO2 composite metal compound electron transport layer: Before spin coating the Sb2O5@SnO2 metal compound composite tin oxide precursor solution of step (4) on the surface of the transparent electrode, place the transparent electrode in UV-ozone plasma treatment for 15 minutes to enhance wettability, take out the plasma-treated transparent electrode, use a pipette to take 100 μL of Sb2O5@SnO2 metal compound composite tin oxide precursor solution, keep the rotation speed at 3000 rpm for 30 seconds, and accelerate at 2000 rpm / s, and spin coat it onto the FTO substrate, and then heat anneal and oxidize at 150°C for 30 minutes;
[0055] Step (7): Solution preparation of perovskite light absorption layer: After the annealed Sb2O5@SnO2 composite metal compound electron transport layer is cooled to room temperature, it is treated with UV-ozone plasma for 8 minutes, and then transferred to a nitrogen glove box. Then, 60 μL of the prepared perovskite precursor solution (step 1) is evenly dropped on the surface of the electron transport layer, and the spin coater program is set to 1000 rpm, 1000 rpm / s, 10s; 5000 rpm, 3000 rpm / s, 30s, and 110 μL of chlorobenzene solution is added in the last 5-3s of the program. After the program is stopped, the film is transferred to a heating plate at 105°C for annealing for 30 minutes;
[0056] Step (8): Hole transport layer deposition: Spin-coat 50-60 μL of hole transport layer solution on the surface of the perovskite light absorption layer, and control the thickness to about 200 nm by controlling the concentration and rotation speed of the solution. The preferred procedure is 4000 rpm, 2000 rpm / s, 30 s, and then place it in a drying cabinet for 24 h;
[0057] Step (9): Electrode deposition: Deposit silver / gold electrodes by thermal evaporation, control the thickness to 80-120 nm, evaporate 5 nm at 0.05 A / s, evaporate to 10 nm at 0.10 A / s, evaporate to 80-120 nm at 0.8 A / s, and then place it in a moisture-proof cabinet.
[0058] Comparative Example 2
[0059] This comparative example is a method for preparing a perovskite solar cell based on only a SnO2 electron transport layer, which comprises the following steps:
[0060] Step (1): Preparation (FAPbI3) 0.9 (MAPbBr3) 0.1 Precursors: PbI2 concentration is 1.53M, PbBr2 concentration is 0.11M, FAI concentration is 1.4M, MABr concentration is 0.11M, MACl concentration is 0.5M, solvent is N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the solvent volume ratio is 9:1, and stirred for 12 to 24 hours to obtain a usable perovskite precursor solution;
[0061] Step (2): prepare and dilute a commercial tin dioxide nanoparticle colloidal dispersion (15 wt%), dilute it according to the ratio of tin oxide colloidal dispersion to deionized water (1:3 mass ratio), stir it at room temperature for 12 hours, and filter it with a filter membrane with a pore size of 0.45 μm for later use;
[0062] Step (3): using FTO conductive glass as substrate and transparent electrode, with a transmittance of 80% and a surface resistance of 15Ω;
[0063] Step (4): Deposition of SnO2 electron transport layer: Before spin coating the alkaline tin oxide colloidal dispersion in step (2) on the surface of the transparent electrode, place the transparent electrode in UV-ozone plasma treatment for 15 minutes to enhance wettability, take out the plasma-treated transparent electrode, use a pipette to take 100 μL of the alkaline tin oxide colloidal dispersion, keep the rotation speed at 3000 rpm for 30 seconds, and the acceleration is 2000 rpm / s, and spin-coat it onto the FTO substrate, and then heat anneal at 150°C for 30 minutes;
[0064] The preparation of the perovskite layer, the hole layer, and the electrode is the same as in Example 2, steps (7-9).
[0065] The material and device performance tests of Example 2 and Comparative Example 2 are as follows:
[0066] like Figure 3 As shown in the figure, comparing the scanning electron microscope (SEM) morphology of the SnO2 electron transport layer and the Sb2O5@SnO2 composite metal compound electron transport layer, the agglomerates of SnO2 nanoparticles can be observed in the SnO2 film, and the Sb2O5@SnO2 film exhibits higher uniformity due to the suppression of aggregation, which is conducive to avoiding direct contact between the FTO and the perovskite layer. This is crucial to ensure low current leakage and suppress non-radiative charge carrier recombination in perovskite solar cells.
[0067] Figure 4The photoluminescence (PL) spectra of SnO2 and Sb2O5@SnO2 films are given. The PL emission of tin oxide nanoparticles is through V O The charge recombination occurs between holes at s and excited electrons in the conduction band or shallow defects on the surface and in the bulk. Therefore, the PL emission peak of the Sb2O5@SnO2 composite metal compound film is weaker than that of the SnO2 film, which confirms the effective passivation of defects and is beneficial to suppress carrier recombination when used as an ETL.
[0068] The solar cells of Example 2 and Comparative Example 2 were placed under standard light intensity (Newport, AM 1.5G, 100 Mw cm -2 The test was carried out under ). The measurement results are as follows Figure 5 The specific battery parameters are shown in Table 1.
[0069] Table 1 Performance parameters of perovskite cells
[0070] sample <![CDATA[V OC (V)]]> <![CDATA[J SC (mA cm -2 )]]> FF(%) PCE(%) <![CDATA[SnO2 electron transport layer]]> 1.13 24.72 80.94 22.60 <![CDATA[Sb2O5@SnO2 composite electron transport layer]]> 1.20 24.75 82.98 24.54
[0071] Example 3
[0072] This embodiment discloses the preparation of a MoO3@SnO2 composite metal compound film:
[0073] Step (1): Preparation of molybdenum trioxide aqueous dispersion: Prepare a molybdenum trioxide aqueous dispersion with a concentration of 0.5-5 mg / ml and stir at room temperature for 3 h;
[0074] Step (2): Synthesis of alkaline tin oxide colloidal dispersion: Mix aqueous solutions of NH4HCO3 (1.0 mol / L) and SnCl4 (1.0 mol / L), stir and react in an ice bath for 3 hours, then stir and react at room temperature for 10 hours, and obtain a milky white tin oxide gel (SnO2·nH2O, n≤2) through hydrolysis and condensation reaction. Wash the gel with deionized water by centrifugation for 5 times, and redisperse the washed wet gel in a mixed solution of potassium hydroxide (2 mg / ml) and ammonia water (PH=12) (the volume ratio of potassium hydroxide to ammonia water is 1:2), and add a mixed dispersant of PVP and CTAB with a mass fraction of 0.15% (wherein m(PVP):m(CTAB)=2:1), stir and react for 3 hours, and obtain a clear and transparent colloidal dispersion (mass fraction is 3.75%), which is filtered with a filter membrane with a pore size of 0.45 μm for standby use;
[0075] Step (3): Preparation of MoO3@SnO2 metal compound composite tin oxide precursor solution: 200 μL of molybdenum trioxide aqueous dispersion with different concentrations (preferably 2.5 mg / ml) is added to 1 ml of tin dioxide nanocolloid dispersion (step 2), and ultrasonically dispersed in an ultrasonic device for 1 h at room temperature to avoid boiling of water in the ultrasonic device. After the ultrasonication is completed, the solution is filtered with a filter membrane with a pore size of 0.45 μm for standby use;
[0076] Step (4): Before spin coating the MoO3@SnO2 metal compound composite tin oxide precursor solution, place the quartz glass in UV-ozone plasma treatment for 15 minutes to enhance wettability, take out the plasma-treated quartz glass, use a pipette to take 100 μL of MoO3@SnO2 metal compound composite tin oxide precursor solution, keep the rotation speed at 1500 rpm for 30 seconds, and the acceleration is 1000 rpm / s. Spin coat it on the quartz glass, and then heat and anneal it at 150°C for 30 minutes.
[0077] Comparative Example 3:
[0078] Step (1): Synthesis of alkaline tin oxide colloidal dispersion: Mix aqueous solutions of NH4HCO3 (1.0 mol / L) and SnCl4 (1.0 mol / L), stir and react in an ice bath for 3 hours, then stir and react at room temperature for 10 hours, and obtain a milky white tin oxide gel (SnO2·nH2O, n≤2) through hydrolysis and condensation reaction. Wash the gel with deionized water by centrifugation for 5 times, and redisperse the washed wet gel in a mixed solution of potassium hydroxide (2 mg / ml) and ammonia water (PH=12) (the volume ratio of potassium hydroxide to ammonia water is 1:2), and add a mixed dispersant of PVP and CTAB with a mass fraction of 0.15% (wherein m(PVP):m(CTAB)=2:1), stir and react for 3 hours, and obtain a clear and transparent colloidal dispersion (mass fraction is 3.75%), which is filtered with a filter membrane with a pore size of 0.45 μm for standby use;
[0079] Step (2): Place the quartz glass in ultraviolet-ozone plasma treatment for 15 minutes to enhance wettability, take out the plasma-treated quartz glass, use a pipette to take 100 μL of the alkaline tin dioxide nanocolloid dispersion of step (1), keep the rotation speed at 1500 rpm for 30 seconds, and the acceleration is 1000 rpm / s, spin-coat it on the quartz glass, and then heat anneal at 150°C for 30 minutes.
[0080] Figure 6The conductivity tests of MoO3@SnO2 composite metal compound film (Example 3) and SnO2 film (Comparative Example 3) are given. By comparison, it can be found that the conductivity of the composite metal compound film is significantly higher than that of the tin oxide film, indicating that the composite film can quickly transport electrons.
[0081] Although the present invention has been disclosed above by describing specific embodiments of the present invention, it should be understood that all the above embodiments and examples are exemplary rather than restrictive. Those skilled in the art may design various modifications, improvements or equivalents of the present invention within the spirit and scope of the appended claims. These modifications, improvements or equivalents should also be considered to be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal compound composite tin oxide nano-colloid dispersion, Features: include: Step 1: obtaining an alkaline tin dioxide colloidal dispersion; Step 2: Preparation of aqueous dispersion of amphoteric metal compound: preparing aqueous dispersion of amphoteric metal compound with different concentrations of 0.5-5 mg / ml, and stirring at room temperature for a preset time; Step 3: Preparation of metal compound composite tin oxide colloidal dispersion: 200 μL of solution was taken from the amphoteric metal compound aqueous dispersions of different concentrations and added to 1 ml of alkaline tin dioxide colloidal dispersion, and ultrasonically dispersed in an ultrasonic device for a certain period of time at room temperature to avoid boiling of water in the ultrasonic device, thereby obtaining a metal compound composite tin oxide precursor solution; Step 4: Deposition of metal compound composite tin oxide film: spin-coat the metal compound composite tin oxide precursor solution prepared in step 3 on the surface of the substrate, and anneal to form a metal compound composite tin oxide film.
2. The method for preparing the metal compound composite tin oxide nano-colloid dispersion according to claim 1, Features: In the step 1, the alkaline tin dioxide colloidal dispersion is obtained by purchasing a commercial Alfa tin dioxide colloidal dispersion, then diluting it in a mass ratio of 1:3 between tin oxide and deionized water and stirring it at room temperature; or it can be synthesized by the following steps: By mixing NH 4 HCO 3 and SnCl 4 The aqueous solution is subjected to hydrolysis condensation reaction to obtain tin oxide gel SnO 2 ·nH 2 O, n≤2, the specific reaction process is described by the reaction formula: SnC 4 +4NH 4 CO 3 →SnO 2 ·nH 2 O+4NH 4 Cl+4CO 2 +(2-n)H 2 O; The reaction is firstly carried out in an ice bath with stirring for a preset time, and then stirred at room temperature for a certain time to generate a milky white gel; the generated milky white gel is centrifugally washed with deionized water for several times to obtain a wet gel, and the washed wet gel is redispersed in a mixed solution of potassium hydroxide and ammonia water, wherein the volume ratio of potassium hydroxide to ammonia water is 1:2, and a mixed dispersant of PVP and CTAB (wherein m(PVP):m(CTAB)=2:1) is added, and the reaction is stirred for a certain time to obtain a clear and transparent colloidal dispersion.
3. The method for preparing the metal compound composite tin oxide nano-colloid dispersion according to claim 2, Features: In step 2, the amphoteric metal compound hydrolyzed in an alkaline environment is: AlCl 3 , SbCl 3 , ZnO, Al 2 O 3 , Sb 2 O 3 , TiO 2 , Nb 2 O 5 , Sb 2 O 5 , WO 3 , or MoO 3 .
4. The method for preparing the metal compound composite tin oxide nano-colloid dispersion according to claim 2, Features: In step 4, before the metal compound composite tin oxide precursor solution of step 3 is spin-coated on the substrate surface, the following treatment is also performed: the substrate is placed in ultraviolet-ozone plasma treatment for several minutes to enhance the wettability of the substrate.
5. The method for preparing the metal compound composite tin oxide nano-colloid dispersion according to claim 4, Features: In step 4, the annealing temperature is 145° C.-155° C., and the annealing time is 25-35 min.
6. Application of a metal compound composite tin oxide colloidal dispersion in chemical sensors, solar cells, recyclable power electrodes, and integrated circuits.
Citation Information
Patent Citations
Surface-modified metal oxide nanoparticle dispersion liquid composition, method for preparing same, thin film composition, and optical thin film
CN114249956A
